Beyond white light: optical enhancement in conjunction with magnification colonoscopy for the assessment of mucosal healing in ulcerative colitis - Iacucci, Marietta; Kiesslich, Ralf; Gui, Xianyong; Panaccione, Remo; Heatherington, Joan; Akinola, Oluseyi; Ghosh, Subrata (Endoscopy, 2017)
Background and study aim The I-SCAN optical enhancement (OE) system with magnification is a recently introduced combination of optical and digital electronic virtual chromoendoscopy, which enhances mucosal and vascular details. The aim of this pilot study was to investigate the use of I-SCAN OE in the assessment of inflammatory changes in ulcerative colitis (UC). Patients and methods A total of 41 consecutive patients with UC and 9 control patients were examined by I-SCAN OE (Pentax Medical, Tokyo, Japan). Targeted biopsies of the imaged areas were obtained. A new optical enhancement score focusing on mucosal and vascular changes was developed. The diagnostic accuracy of I-SCAN OE was calculated against histology using two UC histological scores – Robarts Histopathology Index (RHI) and ECAP (Extent, Chronicity, Activity, Plus additional findings).Results The overall I-SCAN OE score correlated with ECAP (r = 0.70; P < 0.001). The accuracy of the overall I-SCAN OE score to detect abnormalities by ECAP was 80 % (sensitivity 78 %, specificity 100 %). I-SCAN OE vascular and mucosal scores correlated with ECAP (r = 0.65 and 0.71, respectively; P < 0.001). The correlation between overall I-SCAN OE score and RHI was r = 0.61 (P < 0.01), and the accuracy to detect abnormalities by RHI was 68 % (sensitivity 78 %, specificity 50 %). The majority of patients with Mayo 0 had abnormalities on I-SCAN OE.Conclusion In UC, the new I-SCAN OE technology accurately identified mucosal inflammation, and correlated well with histological scores of chronic and acute changes.